2020
DOI: 10.1186/s12889-020-09685-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards tuberculosis in Gambia: a nation-wide cross-sectional survey

Abstract: Background Early diagnosis and treatment of tuberculosis (TB) are the mainstay of global and national TB control efforts. However, the gap between expected and reported cases persists for various reasons attributable to the TB services and care-seeking sides of the TB care cascade. Understanding individual and collective perspectives of knowledge, attitudes, beliefs and other social circumstances around TB can inform an evidence-based approach in engaging communities and enhance their participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 35 publications
10
36
3
5
Order By: Relevance
“…Although the majority (95%) of adults from the study area are aware of TB, less than half (44%) has good overall knowledge about TB infection. In this study, the proportion of the study participants with good overall knowledge is almost the same as that of Nigeria but lower than in the Gambian study [26,27]. The variation in the proportions of population with good knowledge about TB infection between urban and rural in not a new phenomenon.…”
Section: Plos Global Public Healthcontrasting
confidence: 45%
See 3 more Smart Citations
“…Although the majority (95%) of adults from the study area are aware of TB, less than half (44%) has good overall knowledge about TB infection. In this study, the proportion of the study participants with good overall knowledge is almost the same as that of Nigeria but lower than in the Gambian study [26,27]. The variation in the proportions of population with good knowledge about TB infection between urban and rural in not a new phenomenon.…”
Section: Plos Global Public Healthcontrasting
confidence: 45%
“…Despite a larger proportion of adults having good knowledge on symptoms, transmission and good practices about TB infection, it is surprising that as few as only 11% have positive attitudes towards the TB infection. This level is in contrast with recent figures from Nigeria, Gambia and Ethiopia [26,27,37]. In 2019, a study in Nigeria reported a link between education among men and their families and TB knowledge scores [38].…”
Section: Plos Global Public Healthmentioning
confidence: 66%
See 2 more Smart Citations
“…The questionnaire [12] was used to investigate the KAP level of newly treated smear-positive pulmonary tuberculosis patients. The 24 items in the questionnaire included knowledge, attitude, and the behavior of tuberculosis.…”
Section: Questionnaire On the Knowledge Attitudes And Practice Of Newly Treated Smear-positive Pulmonary Tuberculosis Patientsmentioning
confidence: 99%